ANALYSIS OF THE READINESS OF INDONESIAN PEOPLE AND REGULATIONS IN HANDLING FRAUD ON TECHNOLOGY EXPLOITATION - Mustika Prabaningrum Kusumawati; Ari Nur Rahman; Panzi Aulia Rahman; Henry Adrian Sumule; Endrojoyo Sigit Triyono (Association of Certified Fraud Examiners Indonesia Chapter, 2020)
The development of information technology has a big influence in supporting business continuity among producers, consumers, distributors, and financial service institutions. The development of Financial Technology (Fintech) has now become a trend in modern society that follows the current developments. The positive side of technological development, especially in supporting fast and smooth financial services, can actually create a large gap in the readiness of the use of technology in the industrial revolution 4.0. Without strong preparation, this will increasingly create a big gap in the formation of the Fintech technology-based fraud chain. This paper discusses how a qualitative research using the grounded research model can find out the use of recht vacuum loopholes to commit fraud in the exploitation of technology. In addition, it also encourages the establishment of a regulation that supports the creation of a healthy Fintech ecosystem which is the main key in increasing Indonesia's economic growth. Factors influencing the occurrence of fraud include the lack of public knowledge about how to transact using Fintech, the looseness of applicable regulations, the arrogance of Fintech consumer in utilizing bug software Fintech to get profit as much as possible without thinking about legal consequences, the arrogance of the Fintech company in minimizing the large risks that will occur, and not maximum formation of the Fintech ecosystem with other traditional financial service institutions. The situation is exacerbated by the unavailability of the Whistleblowing System (WBS) through a complaint channel specifically for Fintech. The establishment of the Fintech ecosystem, with the adoption of an anti-fraud system as one of the factors that drive Indonesia's economic growth, can be done by creating a technology-savvy community, especially Fintech; making an integrity pact to support anti-fraud and anti-money laundering among regulators, the Fintech association, and the Fintech companies at the time of making official registration with the regulator; Regulators need to get rid of egotism between institutions by synchronizing verbally or nonverbally through technology channels that are automatically integrated between state institutions and preparing special channels for whistleblower systems or consumer complaints channel specifically for Fintech.